Isolating and Identifying Some Types of Bacteria and Fungi from wheat grains and studying the effect of some types of antibiotics and the aqueous and alcoholic extract of the Alium sativum plant on them - GHAJIRI, HADEEL; AL-Gorani, Amal; Saadon, Hanan; Ahmed A. Al-Mankhee, (University of Thi-Qar Journal of Science, 2023)
The study included the effect of Alium sativum aqueous and alcoholic extracts on the growth of bacteria and fungi isolated from the study The following types of bacteria appeared:Pseudomouas aeruginosa ,Aeromonas  salmonicida ,Escherichia  coli Using the diffusion method The aqueous extract was shown to be somewhat higher than the alcoholic extract in inhibiting the above-mentioned bacteria, In the past three decades, disease-resistant fungi and bacteria have emerged it caused major health problems  all over the world through the pharmaceutical industry produced quantities of antibiotics. Unfortunately, resistance to antibiotics is increasingly important. Find plants with antifungal and antibacterial activity it has gained increasing importance in recent years due to the development of resistance. On the other hand, it is known that free radicals play an essential role in many diseases. Biochemical damage caused by free radicals to cells and tissues. If the average inhibition diameters at a concentration of 100% for the aqueous extract were (20.16.18) mm, respectively While the rates of inhibition diameters for the alcoholic extract reached (17,14,16) mm, respectively. As for the fungi isolated from the study, they are: Aspergillus .niger ,Rhizopus stolonifer . : Aspergillus candidus  .Aspergillus fumigatus. Aspergillus  flavus . Aspergillus ochraceus  It was found that the aqueous and alcoholic extracts have an inhibitory effect on the growth of the isolated fungi when using the method of diffusion with the medium